Myanmar Burkholderia pseudomallei strains are genetically diverse and originate from Asia with phylogenetic evidence of reintroductions from neighbouring countries - Webb, JR; Win, MM; Zin, KN; Win, KKN; Wah, TT; Ashley, EA; Smithuis, F; Swe, MMM; Mayo, M; Currie, BJ; Dance, DAB (Springer Nature, 2020)
Melioidosis was first identified in Myanmar in 1911 but for the last century it has remained largely unreported there. Burkholderia pseudomallei was first isolated from the environment of Myanmar in 2016, confirming continuing endemicity. Recent genomic studies showed that B. pseudomallei originated in Australia and spread to Asia, with phylogenetic evidence of repeated reintroduction of B. pseudomallei across countries bordered by the Mekong River and the Malay Peninsula. We present the first whole-genome sequences of B. pseudomallei isolates from Myanmar: nine clinical and seven environmental isolates. We used large-scale comparative genomics to assess the genetic diversity, phylogeography and potential origins of B. pseudomallei in Myanmar. Global phylogenetics demonstrated that Myanmar isolates group in two distantly related clades that reside in a more ancestral Asian clade with high amounts of genetic diversity. The diversity of B. pseudomallei from Myanmar and divergence within our global phylogeny suggest that the original introduction of B. pseudomallei to Myanmar was not a recent event. Our study provides new insights into global patterns of B. pseudomallei dissemination, most notably the dynamic nature of movement of B. pseudomallei within densely populated Southeast Asia. The role of anthropogenic influences in both ancient and more recent dissemination of B. pseudomallei to Myanmar and elsewhere in Southeast Asia and globally requires further study.